Kedisiplinan Siswa Ditinjau dari Dukungan Sosial dan Pola Asuh Otoriter Orang Tua pada Siswa yang Berlatar Belakang Berbeda (Tni dan Non-Tni) - Wicaksono, David Ary (Widya Warta, 2014)
This study aims to determine the student disciplines viewed from social support and parenting authoritarian discipline. The subject of the research was the second - year students of State Junior High School 1 Maospati – Madiun. The total number of the subject was 93 students. This research made use of questionnaires as the measuring instrument. While, the data were analyzed applying two - predictor regression analysis method and one way anava with SPSS program of version 18 The data analysis indicated the correlation coefficient R = 0.903; F regression = 0.197; p = 0.000 (p<0.05). The findings showed there was a significant relationship between social support and parenting authoritarian discipline toward student discipline at school. It also means that social support and parenting authoritarian discipline can be used as predictors of student discipline. Whereas, the difference of parental background had no effects on student discipline. It is proved by the F regression = 3.346; Sig = 0.071, which means that the parents with military (=87.31) and nonmilitary (=85.75) backgrounds had no difference toward student discipline.